Nie tylko Biblioteka. Przedwojenna działalność Domu Oświatowego (11 XI 1934 – 1 IX 1939) (PDF 2,17 MB) (Książnica Śląska, 2025)
The article discusses the history of the Dom Oświatowy from its opening in November 1934 to the outbreak of World War II. Firstly, it recalls the first attempts to create a place for cultural, educational andscientific institutions of the autonomous Silesian Voivodeship, thenthe history of the building’s construction. The main part of the articlepresents the pre-war history of the Dom Oświatowy. All the “tenants”of the building were described as well as their rich and varied cultural and educational activities. The collected material is the result ofa detailed research in two major Katowice daily newspapers: “Polonia” and “Polska Zachodnia”.